Combining Metabolic Analysis With Biological Endpoints Provides a View Into the Drought Resistance Mechanism of Carex breviculmis - Mi, Zhaorong; Ma, Yingying; Liu, Pinlin; Zhang, Haoyi; Zhang, Lu; Jia, Wenqing; Zhu, Xiaopei; Wang, Yanli; Zhang, Chan; Du, Lin; Li, Xilin; Chen, Haitao; et al. (Frontiers in Plant Science, 2022)
Metabolomics is an effective tool to test the response of plants to environmental stress; however, the relationships between metabolites and biological endpoints remained obscure in response to drought stress. Carex breviculmis is widely used in forage production, turf management, and landscape application and it is particularly resistant to drought stress. We investigated the metabolomic responses of C. breviculmis to drought stress by imposing a 22-day natural soil water loss. The results showed that water-deficit restrained plant growth, reducing plant height, leaf fresh weight, and total weight, however, increasing soluble protein content and malondialdehyde content. In total, 129 differential metabolites in the leaves were detected between drought and control using the Ultrahigh Performance Liquid Chromatography-Mass Spectrometer (UPLC-MS) method. Drought enhanced most of the primary and secondary metabolites in the differential metabolites. Almost all the sugars, amino acids, organic acids, phytohormones, nucleotides, phenylpropanoids and polyketides in the differential metabolites were negatively correlated with plant height and leaf fresh weight, while they were positively correlated with soluble protein content and malondialdehyde content. Metabolic pathway analysis showed that drought stress significantly affected aminoacyl-tRNA biosynthesis, TCA cycling, starch and sucrose metabolism. Our study is the first statement on metabolomic responses to drought stress in the drought-enduring plant C. breviculmis. According to the result, the coordination between diverse metabolic pathways in C. breviculmis enables the plant to adapt to a drought environment. This study will provide a systematic framework for explaining the metabolic plasticity and drought tolerance mechanisms of C. breviculmis under drought stress.